Examining the role of psychological factors in the relationship between sleep problems and suicide. (June 2017) - Littlewood, D.; Kyle, S.D.; Pratt, D.; Peters, S.; Gooding, P.
Abstract: We sought to conduct the first systematic review of empirical evidence investigating the role of psychological factors in the relationship between sleep problems and suicidal thoughts and behaviours. Twelve studies were identified which examined psychological factors grouped into four categories of cognitive appraisals, psychosocial factors, emotion regulation strategies, and risk behaviours. Although there was substantial heterogeneity across studies with respect to measurement, sampling, and analysis, preliminary evidence indicated that negative cognitive appraisals, perceived social isolation, and unhelpful emotion regulation strategies may contribute to the association between sleep problems and suicidal thoughts and behaviours. Given that findings in this area are currently restricted to studies with cross-sectional designs, the directionality of the interrelationships between these psychological factors, sleep problems and suicidality, remains unclear. We integrate the findings of our review with contemporary psychological models of suicidal behaviour to develop a clear research agenda. Identified pathways should now be tested with longitudinal and experimental designs. In addition, a more thorough investigation of the complexities of sleep, psychological factors, and suicidal thoughts and behaviours is crucial for the development of targeted psychological interventions. Highlights: Systematic review of the role of psychological factors in sleep/suicide relationships Review findings integrated with suicide theory to define a clear research agenda. Reliance on cross-sectional designs limits interpretation of directionality of pathways. Identified pathways should be investigated with longitudinal and experimental designs.